2018
DOI: 10.1530/rep-17-0658
|View full text |Cite
|
Sign up to set email alerts
|

Effects of colostrum, feeding method and oral IGF1 on porcine uterine development

Abstract: Nursing ensures lactocrine delivery of maternally derived, milk-borne bioactive factors to offspring, which affects postnatal development of female reproductive tract tissues. Disruption of lactocrine communication for two days from birth (postnatal day (PND) 0) by feeding milk replacer in lieu of nursing or consumption of colostrum alters porcine uterine gene expression globally by PND 2 and inhibits uterine gland genesis by PND 14. Here, objectives were to determine effects of: (1) nursing or milk replacer f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In the human endometrium, it was found that IGF-1 participates in the maintenance of an angiogenic phenotype by inducing VEGF expression (Bermont et al, 2000). Furthermore, a recent study reported that IGF-1 is a critical determinant of neonatal porcine uterine development (George et al, 2018). Our results demonstrated that IGF-1 protein expression was directly inhibited by miR-206, which were highly expressed in LL and lowly expressed in ER.…”
Section: Discussionmentioning
confidence: 99%
“…In the human endometrium, it was found that IGF-1 participates in the maintenance of an angiogenic phenotype by inducing VEGF expression (Bermont et al, 2000). Furthermore, a recent study reported that IGF-1 is a critical determinant of neonatal porcine uterine development (George et al, 2018). Our results demonstrated that IGF-1 protein expression was directly inhibited by miR-206, which were highly expressed in LL and lowly expressed in ER.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, a single feeding of colostrum was effective in supporting cervical (Camp et al, 2014) and endometrial cell proliferation at 12 h postnatal (George et al, 2018). In addition, there was no effect of method of delivery of a single dose of colostrum, either by nursing, bottle feeding or orogastric gavage, on uterine developmental markers at 12 h postnatal (George et al, 2018). Collectively, these data indicate that both age at first nursing and duration of nursing are important in neonatal porcine female reproductive tract development, and that lactocrine effects can be detected in nursing piglets within 12 h of birth (Bagnell and Bartol, 2019).…”
Section: Uterusmentioning
confidence: 77%
“…Uterine MMP2 and MMP9 activities, detected by zymography, mirrored immunoblotting data. In other studies, a single feeding of colostrum was effective in supporting cervical (Camp et al, 2014) and endometrial cell proliferation at 12 h postnatal (George et al, 2018). In addition, there was no effect of method of delivery of a single dose of colostrum, either by nursing, bottle feeding or orogastric gavage, on uterine developmental markers at 12 h postnatal (George et al, 2018).…”
Section: Uterusmentioning
confidence: 79%
“…Insulin-like growth factor-I and -II are additionally not believed to permeate the intestine (Blum and Baumrucker, 2002;Hammon et al, 2020), as recombinant human IGF-I was absorbed in negligible quantities from isolated jejunal loops in 1-d old feed-deprived calves (Vacher et al, 1995); however, there is some evidence to the contrary (Skaar et al, 1994;Sparks et al, 2003). Colostral IGF-I absorption by neonatal piglets is also controversial (Xu and Wang, 1996;Burrin, 1997;Donovan et al, 1997); yet, orally supplemented IGF-I in colostrum or milk replacer supported cervical and uterine development in neonatal gilts (Camp et al, 2018;George et al, 2018). This recent data demonstrates that colostral IGF-I can be absorbed by neonates whilst the intestine is hyperpermeable and suggests that its absorption by calves may need to be re-evaluated within the first hours of life, as opposed to 1 d of life (Vacher et al, 1995).…”
Section: Interestingly Female Ruminants Produce Exceptionally High Concentrations Of Ovarian Insl3mentioning
confidence: 99%